2019
DOI: 10.20944/preprints201908.0093.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extraction of Polyphenols and Synthesis of New Activated Carbon from Spent Coffee Grounds

Abstract: A valorization process of spent coffee grounds (SCG) was studied. Thus, a two-stage process, a stage of extraction of the polyphenols and a stage of obtaining activated carbon (AC) by a carbonization process, was performed. The extraction was carried out with a hydro-alcoholic solution in a pressure reactor, modifying time and temperature. To optimize the extraction of polyphenols, a two-level factorial design with three replications at the central values was used. The best results were obtained by performing … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…However, TPC and TFC had a reduction in comparison with the residues of fresh peel (control) of 69.3% and 69.7% and 31.2% and 51.2% ( p < 0.05), but an increase in TAC of 20.7% and 108.3% ( p < 0.05) in conventional drying and lyophilization, respectively. The variation in the levels of polyphenols and antioxidant activity according to the drying conditions applied has been observed in previous studies [ 5 , 15 , 18 , 32 ]. The conditions of thermal processing apparently have a significant effect on these parameters.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…However, TPC and TFC had a reduction in comparison with the residues of fresh peel (control) of 69.3% and 69.7% and 31.2% and 51.2% ( p < 0.05), but an increase in TAC of 20.7% and 108.3% ( p < 0.05) in conventional drying and lyophilization, respectively. The variation in the levels of polyphenols and antioxidant activity according to the drying conditions applied has been observed in previous studies [ 5 , 15 , 18 , 32 ]. The conditions of thermal processing apparently have a significant effect on these parameters.…”
Section: Resultssupporting
confidence: 57%
“…In addition, the results observed in the present study are in agreement with other studies reporting that the phenolic content and antioxidant activity were affected by cooking processes, such as steam, boiling, and drying. Variations in total phenolic content and antioxidant activity according to drying conditions have been reported previously [ 17 , 18 , 32 ].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Practically any raw materials with high carbon content, including several wastes, may yield interesting and useful materials (Deiana et al, 2009 ). Various waste sources have been proposed for the preparation of activated carbon, from biodiesel (Gonçalves et al, 2019 ) to food processing waste (Ramón-Gonçalves et al, 2019 ; Senophiyah-Mary et al, 2019 ; Yaglikci et al, 2020 ) or agriculture industry residues (Ukanwa et al, 2019 ), all of them with great attractiveness owing to their large-scale production and low price. Winemaking-derived waste is a major issue in the wine industry, being Spain, the origin of the precursor wine used in this work, the third world producer of wine (Maicas and Mateo, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…No experiment has been carried out with pH < 0.7 and pH ≥ 14 to confirm that caffeine cation or anion has more affinity for water. Polyphenols like chlorogenic acids are the main impurities in aqueous extract, thus, potentially transferred in ethyl acetate [55,56]. Gazzani et al have reported that chlorogenic acids from green coffee beans were more efficiently extracted in ethyl acetate at acidic pH [57].…”
Section: Influence Of Aqueous Extract Phmentioning
confidence: 99%